Metal injection moulding of NiTi alloy from elemental powder of nickel and titanium using palm stearin based binder system / Rosliza Razali - Razali, Rosliza (2016)
This study presents the processing of NiTi alloy from elemental powder of Nickel (Ni) and Titanium (Ti) mixed with binder system of Palm Stearin (PS) and polyethylene (PE) by using Metal Injection Moulding (MIM) process. The processing of NiTi alloys from elemental Ni and Ti powder mixtures by powder metallurgy (PM) route, particularly by metal injection moulding (MIM) is quite challenging owing to many stages involved which will result significantly on the homogeneity level of the powder mixture and the binder component. It process generally starts with mixing selected powders and binder in the correct proportions. The levels of impurities originated from the binder residue, especially oxygen and carbon need to be kept as low as possible since the values significantly influence the shape memory effect (SME) and pseudo-elasticity (PE) behaviour. Three different atomic fractions of Ni-Ti were investigated; 50-50, 50.4-49.6 and 50.8-49.2 and the powder loading used was 65.5vol%. The feedstock containing the mixture of elemental powders and binder exhibited promising rheological properties, thus resulting successful injection moulding at an optimum temperature of 130°C. The moulded tensile-shaped samples were then underwent solvent extraction using n-heptane solution to remove the primary binder of PS. It was followed by thermal debinding to completely remove the backbone binder of PE and subsequently sintered in high vacuum at 1050, 1100 and 1150°C to allow diffusion of the elemental Ni and Ti powders to form NiTi alloy. The XRD results showed that the predominant phases were B2 (austenite) and B19'(martensite) with minimal fractions of Ti-rich phases (NiTi2/Ni2Ti4Ox) and Nirich phases (NisTi and Ni4Ti3) was obtained in the sintered parts. The phases were confirmed by microstructural image from FESEM that showed different grayscale contrast attributed to different atomic mass of the phases. The DSC results showed that increasing Ni content resulted in broadening of reversible martensite to austenite PTTs and decreasing the enthalpy for phase transition. Besides that, the impurities and fractions of secondary phases introduced in the alloy could also the other factors in broadening of phase transformation temperatures (PTTs). The tensile test showed that the samples exhibited promising mechanical tensile properties with the Young's modulus calculated from the stress-strain curve in the range of 2.5 to 4.8 GPa which is close to cancellous type bone. The porous structure shown in SEM images was highly inter-connected, thus promoting better bone tissue ingrowth when it is used as an implant. Increasing Ni contents resulted in slightly increase in degree of ductility which attributed from less fraction of porosity in the samples. Overall, NiTi parts with different Ni-Ti ratios were successfully produced by MIM using palm stearin based binder system.